Tingkat pengetahuan masyarakat tentang penggunaan tanaman herbal sebagai salah satu pencegah covid-19 - Anna Yuliana; Lina Rahmawati; Salsabila Adlina (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: COVID-19 is a disease currently sweeping the world. COVID-19 arises because of a new type of virus called Coronavirus. The existence of this pandemic makes people have to always keep a distance from someone and also comply with health rules when doing activities outside the home. Experts are trying to create a vaccine to fight this virus. One of the ways to protect ourselves from being exposed to this virus is by maintaining the body's immunity using herbal plants. By consuming herbal plants, immunity in the body can be increased due to the nature of herbal plants which can prevent (preventive) through the secondary metabolites contained therein.Objective: The purpose of this study is to see how much public knowledge is about herbal plants and their use as a preventive measure against COVID-19.Methods: This research was conducted with a questionnaire as a medium for data accumulation and the data were analyzed univariately. The form of this research is quantitative with a descriptive survey design in the community.Results: The results of the analysis obtained public knowledge about the use of herbal plants in the good category, namely 89.9%.Conclusion: Public knowledge about the use of herbal plants in the good category.